ABCC6 deficiency is associated with activation of BMP signaling in liver and kidney. Issue 1 (23rd March 2015) - Blazquez-Medela, Ana M.; Guihard, Pierre J.; Yao, Jiayi; Jumabay, Medet; Lusis, Aldons J.; Boström, Kristina I.; Yao, Yucheng
Abstract : Mutations in ABCC6 (ATP‐binding cassette, subfamily C, member 6), an orphan transporter expressed in the liver, are the cause of pseudoxanthoma elasticum. Since ABCC6 was reported to affect matrix Gla protein (MGP), an inhibitor of bone morphogenetic proteins (BMPs), we studied BMP signaling and expression in various tissues of mice with and without functional ABCC. Enhanced BMP signaling was found in all examined tissues in the absence of ABCC6. Despite this, the expression of particular BMP proteins varied widely between tissues. Interestingly, the expression of most BMP proteins in the liver moved in the opposite direction to the same BMP proteins in kidneys in response to ABCC6 alterations. Thus, ABCC6 deficiency stimulates BMP signaling by acting on the expression of multiple BMPs. Abstract : ABCC6 deficiency stimulates BMP signaling in multiple organs. ABCC6 deficiency causes tissue‐specific induction of BMP‐related genes. Tissue‐specific targeting of BMP signaling may be needed in ABCC deficiency.